Comparison of neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR) and platelet-to-lymphocyte ratio (PLR) between dogs with chronic renal failure and clinically normal dogs - Chin-on, Athicom; Lekcharoensuk, Chalermpol (Journal of Mahanakorn Veterinary Medicine, 2024)
Chronic renal failure (CRF) is a common disease in elderly dogs. This condition significantly impacts their quality of life and increases mortality rates. There are many causes of this disease. Inflammation plays a crucial role in CRF, affecting up to 30% of cases. Elevating white blood cell and platelet counts are associated with inflammatory process. The objectives of this study were to compare neutrophil-to-lymphocyte (NLR) ratio, monocyte-to-lymphocyte (MLR) ratio, and platelet-to-lymphocyte ratio (PLR) between dogs with CRF and clinically normal dogs. Data were collected and analyzed from 55 dogs with CRF and 57 clinically normal dogs. The study found statistically significant differences (P<0.05) that dogs with CRF had the values of NLR = 8.33±7.48, MLR = 0.64±0.64 and PLR = 2.98±2.95 higher than clinically normal dogs that had the values of NLR = 3.79±2.25, MLR = 0.26±0.16 และ PLR = 1.71±0.80. The receiver operating characteristic (ROC) curve showed that the areas under curve (AUC) of NLR, MLR, and PLR were 0.70, 0.72, and 0.60, respectively. From all studied data, it was found that the MLR values ​​were significantly different. Using these MLR values ​​to help monitor and evaluate the chronic renal failure in the future should be further studied.